Growth rate, mortality rate and life cycle of Rafflesia azlanii and R. cantleyi in Belum-Temenggor Forest Complex, Perak, Malaysia - Syarifah Haniera Sheikh Kamal; Mohd Nazip Suratman; Shamsul Khamis; Ahmad Najmi Nik Hassan; Mohd Syaiful Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2022)
The life cycle of Rafflesia is very complex because it involves the invisible and visible parts of its growth. The invisible part refers to its penetration, inoculation of the seeds into the host’s tissue and seed formation whereas the visible part is the floral structure that is exposed to the external environments. Currently, there is little information on the life cycle of Rafflesia, therefore knowledge regarding its life cycle is crucial for a successful monitoring of the species as part of conservation efforts. The objectives of this study were to analyse the growth of flower buds at various developmental stages and mortality rates of Rafflesia azlanii and R. cantleyi, and to observe the life cycle of the two species. The growth rate of R. azlanii and R. cantleyi were recorded monthly for five months beginning from an emergence of buds to full bloom in the study sites of Belum-Temenggor Forest Complex, Perak. The buds were measured and vertically photographed for every observation and categorized into eight stages. R. azlanii buds grew at the mean rate of 0.20 cm/day and R. cantleyi was at 0.26 cm/day. This suggests that R. azlanii exhibited a slower growth rate than R. cantleyi. In addition, the mortality rate of R. azlanii (28%) was lower than R. cantleyi (45%). The high mortality rate could be due to two factors; an exposure of the plants to direct sunlight and damage caused by pests. Meanwhile, the life cycle for the visible stage for R. azlanii was 14 months and R. cantleyi was 11 months. The information gathered from this study is useful for field monitoring and observation of the plants for conservation purposes.